2018
DOI: 10.1074/mcp.ra118.000708
|View full text |Cite
|
Sign up to set email alerts
|

CTGF/VEGFA-activated Fibroblasts Promote Tumor Migration Through Micro-environmental Modulation

Abstract: Fibroblast activation is associated with tumor progression and implicated in metastasis, but the initial triggering signals required to kick-start this process remain largely unknown. Because small cancerous lesions share limited physical contact with neighboring fibroblasts, we reasoned the first tumor-derived signal for fibroblast activation should be secreted and diffusible. By pulsed metabolic labeling and click-chemistry based affinity enrichment, we sieved through the ductal carcinoma secretome for poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…CTGF/CCN2 plays a vital role in tumor-stromal interaction and desmoplasia in PDAC (20,(43)(44)(45). Recent studies have shown that tumor cell-derived CTGF is a prerequisite signal for fibroblast activation (56). Because our current studies found that CTGF expression in pancreatic cancer cells and fibroblast cells is regulated by CYR61/CCN5 ( Fig.…”
Section: Maity Et Almentioning
confidence: 48%
“…CTGF/CCN2 plays a vital role in tumor-stromal interaction and desmoplasia in PDAC (20,(43)(44)(45). Recent studies have shown that tumor cell-derived CTGF is a prerequisite signal for fibroblast activation (56). Because our current studies found that CTGF expression in pancreatic cancer cells and fibroblast cells is regulated by CYR61/CCN5 ( Fig.…”
Section: Maity Et Almentioning
confidence: 48%
“…To demonstrate the utility of PhosID in a more relevant cellular context, we applied our optimized protocol to investigate Interferon-gamma (IFNγ) stimulation in two different cell lines. We adopted a classical AHA labeling workflow 41 to introduce 'click-able' azide functionalities into NSPs in HeLa and Jurkat cells, and then applied the PhosID strategy to identify NSPs induced by IFNγ in 4 or 24 h (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, the AKI also resulted in ambiguous epithelial/stromal identities. The heat map shows that the "Mixed Identity Cells" exhibit increased expression of stromal genes, particularly activated fibroblast markers (Ctgf, Col1a2, Cald1) (Shieh et al, 2019;Wu et al, 2018;Zhang et al, 2017b) ( Figure 1F) and genes related to the cell shape change and extracellular matrix remodeling (Sparc, Lgals3, Spp1, Myh9, S100a10) (Table S1), giving evidence for a more mesenchymal phenotype acquired by these cells in response to the injury. Epithelial-to-mesenchymal plasticity is a crucial contributor to the kidney injury and fibrosis (Humphreys, 2018;Lovisa et al, 2016).…”
Section: Cells In the Ischemia Reperfusion Induced Akimentioning
confidence: 99%